2020
DOI: 10.1038/s41598-020-57684-6
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal properties of whisker-evoked tactile responses in the mouse secondary somatosensory cortex

Abstract: The representation of rodents' mystacial vibrissae within the primary somatosensory (S1) cortex has become a major model for studying the cortical processing of tactile sensory information. However, upon vibrissal stimulation, tactile information first reaches S1 but also, almost simultaneously, the secondary somatosensory cortex (S2). To further understand the role of S2 in the processing of whisker inputs, it is essential to characterize the spatio-temporal properties of whisker-evoked response dynamics in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 52 publications
1
33
1
Order By: Relevance
“…In wS1, the spatial organization of VPM-FO axon activity was consistent with whisker specific barrels. In contrast, the somatosensory map of wS2 is less clearly defined than the one observed in wS1 48 , and we found spatially intermingled thalamic axons with different whisker-selectivities. However, in our experiments we only imaged small fields of view, and we only stimulated neighboring whiskers, and thus our results do not exclude that POm-FO axons are spatially functionally organized somatotopically at a larger scale.…”
Section: Discussioncontrasting
confidence: 84%
“…In wS1, the spatial organization of VPM-FO axon activity was consistent with whisker specific barrels. In contrast, the somatosensory map of wS2 is less clearly defined than the one observed in wS1 48 , and we found spatially intermingled thalamic axons with different whisker-selectivities. However, in our experiments we only imaged small fields of view, and we only stimulated neighboring whiskers, and thus our results do not exclude that POm-FO axons are spatially functionally organized somatotopically at a larger scale.…”
Section: Discussioncontrasting
confidence: 84%
“…However, limited attention has been afforded to S1-HP responses. One striking feature of our findings for L2/3 pyramidal of the S1-HP region was the long latency of their stimulus-evoked responses compared with S1-BC (Crochet and Petersen, 2006;Crochet et al, 2011;Gambino et al, 2014;Hubatz et al, 2020;Jouhanneau et al, 2014) and FP stimulation in mice (Zhao et al, 2016), and may reflect the functional role of HP information for the animal. Whisker stimulation evokes a fast depolarizing response with ~9 ms latency in L2/3 pyramidal neurons (Brecht et al, 2003;de Kock et al, 2007;Higley and Contreras, 2005;Jouhanneau et al, 2014;Petersen et al, 2003), in coherence with the role of whiskers for sensory processing with high temporal precision.…”
Section: Discussionmentioning
confidence: 61%
“…A number of studies have examined the response properties of neurons in wS2 after whisker deflection and have found that they have larger receptive fields than neurons in wS1 (Goldin et al 2018;Kwegyir-Afful and Keller 2004). This also matches the less segregated representation of individual whiskers seen with VSDI, suggesting the integration of individual whisker responses from wS1 to wS2 (Hubatz et al 2020). In this study, we examined when and how wS1 begins communicating with wS2 over the course of postnatal development, in order to assess when higher-order processing of whisker stimuli commences.…”
Section: Discussionmentioning
confidence: 74%
“…The sequential engagement of cortical regions in processing sensory stimuli has its prototypical example in the visual system and the two identified streams of information flow in primates and potentially rodents (Glickfeld and Olsen 2017;Stone, Dreher, and Leventhal 1979). In the rodent whisker-related somatosensory cortex, this process involves not only the activation of the primary cortical region, called the barrel cortex (wS1), but also of the secondary region (wS2), two areas which have been found to be activated upon a tactile event received by the whiskers (Condylis et al 2020;Feldmeyer et al 2013;Hubatz et al 2020). Even though wS2 receives direct inputs from the thalamus, specifically the POm and the ventral lateral part of the VPM (VPMvl) (Chakrabarti and Alloway 2006;El-Boustani et al 2020), which can provide its direct sensory stimulus-driven activation, it also receives connections from wS1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation